Strategi Pemasaran Dalam Meningkatkan Daya Saing Usaha Kecil dan Menengah - Pakpahan, Nadin I; Rosalina Hutauruk; Manalu, Violine (Jurnal Ekonomi Manajemen Dan Bisnis (JEMB), 2026)
At this stage of research, SME strategy plays a very important role in the 4.0 era. In this 4.0 era, SMEs have an important role in economic development in Indonesia, but by having an important role, SMEs also have quite big challenges to sales in the marketing stage. So, with this, we need to know how the marketing stage is in the digital era 4.0 and can adapt to the global market. From the research, it produces an understanding of consumer desires, the use of social media, and product innovation, as well as improving product quality to increase the competitiveness of SMEs. On the other hand, the use of social media will also expand market reach and build sales relationships. Thus, the implementation of a good and creative marketing strategy will be one of the effective ways to maintain competition in the 4.0 era.